Composition, antioxidant, and anti-biofilm activity of anthocyanin-rich aqueous extract from purple highland barley bran. (May 2020) - Zhang, Yongzhu; Lin, Yanfei; Huang, Lu; Tekliye, Mekonen; Rasheed, Hafiz Abdul; Dong, Mingsheng
Abstract: Anthocyanin-rich cereal grains have attracted considerable attention recently due to their health benefits in humans. In this work, purple highland barley bran (PHBB) from the Tibetan Plateau in China was evaluated. Results showed that the anthocyanins in PHBB were easily extracted by water in 10 min, and demonstrated good stability under high extraction temperature. The extracts were further purified by AB-8 resin for composition and antioxidant analysis, and the concentration factor increased by about 62-fold in the final purified powder. Anthocyanins in PHBB were analyzed by liquid chromatography-mass spectrometry (LC-MS), and findings showed a complex and high acylated anthocyanin profile with cyaniding malonyl glucoside making up 73.50 ± 3.49% of the total anthocyanin content (TAC) for the first time. Anthocyanin-rich aqueous extract exhibited exceptional antioxidant capacities and remarkable anti-biofilm properties. Therefore, this study strongly suggested that the extracts of PHBB could be used as a high-quality natural food colorant and functional ingredient. Highlights: Anthocyanins in purple highland barley bran was easily extracted by the water. Anthocyanins in purple highland barley bran possessed a good stability. Anthocyanins in purple highland barley bran was highly acylated. Anthocyanins-rich extract exhibited obvious antioxidant capacity. Anthocyanins-rich extract exhibited obvious anti-biofilm properties.